Effects of different deodorising processes on the off‐odour compounds and gel properties of common carp surimi. (17th April 2018) - Jin, Ritian; Meng, Ran; Zhang, Huimin; Yang, Xiaofei; Wu, Zhaoxia
Summary: In order to improve the utilisation of the common carp ( Cyprinus carpio ), the effects of deodorising agents [NaCl, β‐CD, malic acid (MA) and hawthorn extract (HE)] on the volatile compounds of common carp mince and its surimi gel properties were investigated. In total, thirty‐two volatile compounds were identified, seven of which were considered the main compounds of off‐odour, using HS‐SPME‐GC‐MS and OVA analyses. HS‐SPME‐GC‐MS analysis showed that MA and HE removed 84.51% and 77.18% off‐odour compounds, respectively. Three relaxation components ( T 21, T 22, T 23 ) were found in surimi, and their amounts were not affected by deodorising; however, the relaxation time of major component T 22 was significantly increased. Surimi deodorised by HE had the highest gel strength because of its increased breaking displacement; however, a slight decrease in whiteness was observed. Thus, appropriate levels of HE could improve the palatability of surimi. Abstract : Deodorising processes of common carp surimi.